Chicken Ovalbumin Upstream Promoter Transcription Factor II Regulates Renin Gene Expression - Mayer, Sandra (American Society for Biochemistry and Molecular Biology, 2012)
This study aimed to investigate the possible involvement of the orphan nuclear receptor chicken ovalbumin upstream promoter transcription factor II (COUP-TFII) in the regulation of renin gene expression. COUP-TFII colocalized with renin in the juxtaglomerular cells of the kidney, which are the main source of renin in vivo. Protein-DNA binding studies demonstrated that COUP-TFII binds to an imperfect direct repeat COUP-TFII recognition sequence (termed hereafter proxDR) in the proximal renin promoter. Because cAMP signaling plays a central role in the control of the renin gene expression, we suggested that COUP-TFII may modulate this cAMP effect. Accordingly, knockdown of COUP-TFII in the clonal renin-producing cell lines As4.1 and Calu-6 diminished the stimulation of the renin mRNA expression by cAMP agonists. In addition, the mutation of the proxDR element in renin promoter reporter gene constructs abrogated the inducibility by cAMP. The proxDR sequence was found to be necessary for the function of a proximal renin promoter cAMP-response element (CRE). Knockdown of COUP-TFII or cAMP-binding protein (CREB), which is the archetypal transcription factor binding to CRE, decreased the basal renin gene expression. However, the deficiency of COUP-TFII did not further diminish the renin expression when CREB was knocked down. In agreement with the cell culture studies, mutant mice deficient in COUP-TFII have lower renin expression than their control strain. Altogether our data show that COUP-TFII is involved in the control of renin gene expression.